Reengineering the corporation : a manifesto for business revolution - Hammer, Michael, 1948-2008.; Champy, James, 1942- (New York : HarperBusiness Essentials, 2003)
The most successful business book of the last decade, Reengineering the Corporation is the pioneering work on the most important topic in business today: achieving dramatic performance improvements. This book leads readers through the radical redesign of a company's processes, organization, and culture to achieve a quantum leap in performance. Michael Hammer and James Champy have updated and revised their milestone work for the New Economy they helped to create -- promising to help corporations save hundreds of millions of dollars more, raise their customer satisfaction still higher, and grow ever more nimble in the years to come.--PUBLISHER DESCRIPTION.
Prologue : reengineering for the twenty-first century -- The crisis that will not go away -- Reengineering : the path to change -- Rethinking business processes -- The new world of work -- The enabling role of information technology -- Who will reengineer -- The hunt for reengineering opportunities -- The experience of process redesign -- Embarking on reengineering -- One company's experience : Duke Power -- One company's experience : IBM -- One company's experience : Deere -- Succeeding at reengineering -- Epilogue -- Frequently asked questions (FAQs) -- Index.
"A HarperBusiness book."
"Revised and updated with a new author's note"--Cover.
Revised edition of the c2001 ed.
Includes index.
Keywords: Organizational change; Reengineering (Management); Organizational Innovation; Organizational change